THE INFLUENCE OF LEARNING STRATEGIES AND SOCIAL INTERACTIONS ON THE LEARNING OUTCOMES PKn OF GRADE V STUDENTS AT SD NEGERI 014711 SIPARE-PARE IN BATUBARA DISTRICT - Dimas Agung Prasetyo; Reh Bungana Br. Perangin-angin; Daulat Saragi (Jurnal Ilmiah Teunuleh, 2020)
This study aims to find out: (1) differences in students' PKn learning outcomes using Discovery Learning learning strategies with Student Team Achievement Division (STAD) learning strategies, (2) differences in student PKn learning outcomes have cooperative social interactions with competitive social interactions, and (3) interactions between learning strategies and social interactions with students' PKn learning outcomes. The population of this research is grade V students of SD Negeri Negeri 014711 Sipare-Pare and grade V of SD Negeri 013869 Indrapura with a total of 58 people. The sample of this study was determined grade V SD Negeri 014711 Sipare-Pare = 30 following the learning strategy of Discovery Learning and grade V SD Negeri 013869 Indrapura = 28 following the learning using the STAD strategy. Research instruments to measure learning outcomes used multiple-choice form tests and questionnaires for student social interaction. Data analysis techniques use a two-track ANAVA at the level of ? significance = 0.05. The conclusion of the study is (1) The learning outcomes of PKn students in Discovery Learning class are higher than the Student Team Achievement Division class, (2) PKn students' learning outcomes have higher cooperative social interactions than students' learning outcomes have competitive social interactions, (3) There are interactions between learning strategies and social interactions of students in influencing students' PKn learning outcomes.